Rolling Horizon Procedure on Controlled Semi-Markov Models. The Discounted Case - Vecchia, Eugenio Della (2011)
We study the behavior of the rolling horizon procedure for semi-Markov decision processes, with infinite-horizon discounted reward, when the state space is a Borel set and the action spaces are considered compact. We prove the convergence of the rewards produced by the rolling horizon policies to the optimal reward function, when the horizon length tends to infinity, under different assumptions on the instantaneous reward function. The approach is based on extensions of the results obtained in [7] for the discrete-time Markov decision process case and in [3] for the case of discrete-time Markov games. Finally, we also analyse the performance of an approximate rolling horizon procedure.